Chinese language and its implications for business success in China. - Siah, Brenda Pei Peng. (2008)
The focus of this research is to find out the relationship between the knowledge of Chinese language and business success in China by using the four determinants, namelyawareness of cultural values, establishment of guanxi network, smooth flows of negotiation and effective ways of communication skills. This study will also observe if the knowledge of Chinese language is related to each of the fourfactors.